Low-molecular-weight chondroitin sulfate attenuated injury by inhibiting oxidative stress in amyloid β-treated SH-SY5Y cells. Issue 14 (26th September 2018) - Zhang, Qian; Na, Zhao; Cheng, Yanna; Wang, Fengshan
Abstract : The neurotoxicity of aggregated amyloid β (Aβ) has been implicated as a critical cause in the pathogenesis of Alzheimer's disease. In a previous work, we have shown that low-molecular-weight chondroitin sulfate (LMWCS), a derivative of chondroitin sulfate, protected the SH-SY5Y neuroblastoma cells from Aβ25–35 -induced neurotoxicity, decreased intracellular reactive oxygen species level and inhibited the cell apoptosis. However, the underlying mechanism of the antioxidative effect of LMWCS in the SH-SY5Y cells has not been well explored. In the present study, the SH-SY5Y cells were cultured and exposed to 30 μM Aβ25–35 in the absence or presence of LMWCS (50, 100 and 200 μg/ml). Results indicate that incubation of cells with LMWCS before Aβ25–35 exposure increased superoxide dismutase, glutathione peroxidase and Na + /K + -ATPase activities and decreased the malondialdehyde content. In addition, LMWCS inhibited the imbalance of Bcl-2 and Bax and decreased caspase-3 and caspase-9 expressions. LMWCS antagonizes Aβ25–35 -induced neurotoxicity by attenuating oxidative stress, and our results suggest that LMWCS might be used as a potential compound for Alzheimer's disease prevention.